Museums: agents of innovation and transformation (Cadernos de Sociomuseologia, 2019)
We live in a period of profound transformations and challenges in the most varied fields and that dilute political, economic, ethical, aesthetic and ethnic borders, and when the new technological and communication platforms transform our perception and existence. Museums have become anchors of memory and belonging, but they can not be restricted to replication and stagnation. This article aims to discuss the possibility of mutation of this institution. For this, it discusses a number of dimensions and potentialities, such as the role of collections in museums; its symbolic dimension; its versatility; its existence as a polymorphic museum, world museum, museum forum, and in its role in the face of human and social emergencies and as an agent of transformation.Keywords: Museums; Transformation; Collections; World Museum; Museum Forum; polymorphic museum.